Designed physical activities targeting social skills in preschoolers: a meta-analysis - Yuan, Yuxin; Liu, Wen; Yi, Jingyao; Li, Xiaofen (Frontiers in Psychology, 2025)
ObjectivesTo comprehensively evaluate the impact of Designed Physical Activities (DPA) on the social skills of preschoolers, as well as its specific subdomains.MethodsWe obtained data from Web of Science, EBSCO, cochrane library, PubMed, PsycInfo, China National Knowledge Infrastructure, WanfangData, and VIP Data from the establishment of each databases to June, 21, 2024. Two researchers independently assessed the quality of the study using the Cochrane risk of the bias assessment tool. Meta-analysis was performed when data were available, with further subgroup analysis, using Review Manager 5.4, and sensitivity analysis was performed using Stata software 15.1.ResultsSearch terms yielded 7,074 articles, of which 14 fulfilled the inclusion criteria. Results showed that DPA had beneficial effects for social skills [SMD = 0.63, p < 0.0001], and insignificant positive effects for emotional skill [SMD = 1.86, p = 0.08]. Subgroup analysis indicated that interventions with both music and tools, and without music or tools caused positive effects, while those with only music or only tools did not. Considerable outcomes were achieved regardless of the frequencies of the intervention. Interventions of 12 weeks and had a significant effect in promoting preschoolers’ social skills. Notably, the outcomes reported by parents were significantly higher than that reported by teachers and tested by children.ConclusionDPA can significantly improve social skills and emotional skill in preschoolers. Nevertheless, it is imperative to conduct further trials with meticulous and rigorous study designs in order to furnish more definitive evidence in the foreseeable future.